Biochemical and structural characterization of cross-linked enzyme aggregates immobilized elastase strain K - Mohd Razib, Muhammad Syafiq (2020)
Immobilization of enzyme is a great modification technique that enhances the stability and reusability of an enzyme. Nevertheless, some immobilization techniques have low productivity and require the enzyme to undergo purification process; a process which is laborious and time consuming. CLEA immobilization technique offer better alternative since crude enzyme can be used directly during the preparation of CLEA. In this study, CLEA immobilization technique was tailored and developed to retain and enhance the activity of elastase strain K, while facilitating its recovery after completion of an enzymatic reaction. Another area that has been elusive regarding CLEA is the structural analysis. Organic solvent tolerant protease, elastase strain K was immobilized using CLEA technique and the biochemical as well as the biophysical profiles of CLEA-elastase was analyzed. This valuable enzyme exhibit remarkable tolerance against wide range of organic solvents including methanol, ethanol, 1-propanol and dimethyl sulfoxide (DMSO). Aggregates of elastase strain K was prepared by adding 60% (w/v) ammonium sulfate and treated for 3 h prior to cross-linking with 0.2% (v/v) glutaraldehyde for 2 h. Maximum recovered activity of CLEA-elastase was recorded at 61.4% while CLEA-elastase-SB; derivatives of CLEA-elastase with addition of BSA and starch as co-aggregants, recorded a recovered activity of 81.6%. Immobilized elastase strain K exhibit enhanced thermostability and exhibit increment of optimum temperature at 50°C. In addition to that, CLEA-elastase exhibit broad pH stability between pH 5-10 and high proteolytic activity was recorded at pH 8. The organic solvent tolerant characteristic of elastase strain K was retained even after immobilization. Enhancement of organic solvent tolerance was also detected in CLEA-elastase treated with methanol, acetonitrile, ethanol, 1-propanol, benzene and xylene with 111.4%, 164.6%, 172.7%, 111.4%, 152.7% and 133.2% of recovered activity, respectively. The biophysical analysis conducted using scanning electron microscopy (SEM), dynamic light scattering (DLS), Brunauer-Emmett-Teller (BET) surface area and Fourier-transform infrared (FTIR) spectra revealed that CLEA-elastase exhibit a type 2 aggregate morphology; appearance of aggregates are random and less defined, with an average diameter of 1497 nm. In addition, co-aggregation with BSA and starch increase the surface area and porosity of CLEA-elastase. Stretching and vibration of bonding associated with the presence of successful cross-linkages was detected especially within the 1600 – 1700 cm-1 of FTIR spectra. In general, organic solvent tolerant elastase strain K has been successfully immobilized using CLEA method. The technique has successfully being tailored and developed to retain and enhance the proteolytic activity of elastase strain K.